COMPARISON OF EFFICACY AND POSTOPERATIVE COMPLICATIONS BETWEEN UNIPOLAR ELECTROCAUTERY AND BIPOLAR ELECTROCAUTERY IN CASES OF ANTERIOR EPISTAXIS: A RANDOMIZED CONTROL TRIAL - Khan, Muhammad Ahmed; Akram, Sumera; Khan, Muhammad; Bin Usman, Hassan (Journal of Postgraduate Medical Institute, 2017)
Objective: To compare the efficacy and post-operative complications between unipolar electrocautery and bipolar electrocautery in cases of anterior epistaxis. Methodology: Total 60 patients fulfilling the inclusion criteria were selected from ENT outpatient department of CMH Bahawalpur from January 2016 to June 2016. The randomly divided patients of Group A (n=30) underwent cauterization with unipolar cautery while Group B (n=30) patients with bipolar cautery. Both procedures were compared in terms of efficacy (no re-bleed) and complications (post-operative pain, infection and septal perforation). Results: The mean age of the participants was 26.35 ±13.3 years with 33 male and 27 female participants. No significant difference was noted in the post-operative bleeding after bipolar and unipolar procedure (p=0.313); showing both procedures to be equally effective. The groups were assessed for pain and infection on 1st and 5th postop day. Both the procedures had insignificant difference of pain on first postop day (p=0.07). However, there was significant difference of pain on 5th postop day (p=0.023). In Group A two cases developed postoperative infection compared to one case in Group B, but this difference between both procedures was not significant (p=0.554). There was no septal perforation in both groups. Conclusion: Unipolar and bipolar cautery procedures are equally effective in controlling epistaxis with almost negligible postoperative infection. As far as postoperative pain is considered, bipolar cautery is less painful procedure than unipolar cautery.